Design of Hearing Aid and Speech Device for People Hearing Dissorders - Feri Adriyanto; Henry Probo Santoso; Andayani Yuwana Sari; Rizki Misbakhus Suroya (Journal of Electrical, Electronic, Information, and Communication Technology, 2022)
Deafness is a condition in which a person cannot hear due to a disturbance in his hearing organs. In communicating, most of the deaf sufferers only receive hearing aids. WHO (World Health Organization) initiated the Sound of Hearing 2030 by preventing hearing loss by 50% in 2015 and 90% in 2030. The main objective of Sound of Hearing is to develop a comprehensive, inclusive, and sustainable ear care program. Various studies on tools for deafness have been developed. However, this tool is only used to help deaf hearing but not to help speech learning (learn to speak). Thus we need hearing aids and speech learning tools for the deaf. This tool can be a government program, namely supporting a diffable-friendly Indonesia. The tool is designed like a headband, where the headband is composed of a row of vibrating modules that will be connected to the Google Assistant on a smartphone, so that any sound received by the Google Assistant will be sent to the tool to be converted into a vibration pattern. It is from these vibration patterns that a deaf person will get experience in recognizing sounds and learn to speak based on the vibration patterns that are formed. With the design of this tool, it hoped that it can help deaf people and get support from the community and government to create a diffable-friendly Indonesia.